Feature Extraction Techniques in Hyper Spectral Data Sets for Classification Purpose - Rapaka, Anuj; Ramu, Arul Murgan (International Journal of Computer Sciences and Engineering, 2025)
A critical increment for utilization of proximal/remote hyper spectral imaging frameworks to contemplate plant properties, types, and conditions. Various budgetary and ecological advantages of utilizing such frameworks have been the driving constrain inside this development. This paper is worried about the examination of hyper spectral information for identifying plant sicknesses and stress conditions and ordering crop types by methods for cutting edge machine learning strategies. Primary commitment of the work lies in the utilization of an inventive order system for the examination, in which versatile component choice, curiosity recognition, and troupe learning are coordinated. Three hyper spectral datasets and a nonimaging hyper spectral dataset were utilized in the assessment of the proposed structure. Show critical upgrades accomplished by the proposed technique contrasted with the utilization of exact ghastly lists and existing arrangement techniques.